레녹스 가스토 증후군을 가진 소아에서 Rufinamide의 효과 및 안전성 - 민소윤(Soyoon Min); 조태경(Taekyoung Jo); 서효림(Hyorim Suh); 노다은(Daeun Roh); 황수경(Su-Kyeoung Hwang); 이윤정(Yunjeong Lee); 권순학(Soonhak Kwon) (Annals of Child Neurology(구 대한소아신경학회지), 2017)
목적: 레녹스-가스토 증후군은 소아기에 발생하는 뇌전증 중 가장 심한 형태의 뇌전증성 뇌병증으로 알려져 있으며 여러 항경련제 치료에도 불구하고 잘 조절되지 않아 난치성 뇌전증으로 분류된다. 본 연구의 목적은 레녹스-가스토 증후군 소아에서 rufinamide 의 효율성 및 내약성을 분석하고자 하였다. 방법: 본 연구는 레녹스-가스토 증후군으로 진단되어 경북대학교소아청소년과에서 진료받은 환자 중 2011년 1월 1일부터 2014년 12 월 31일까지 rufinamide를 새로 처방 받은 32명을 대상으로 rufinamide 투여 전과 투여 후 4주 간격으로 임상적 특징과 약효와 부작용에 대해 후향적으로 분석하였다. 결과: 남자는 20명 여자는 12명 이었으며 평균연령은 11.3세±6.6 세 였다. Rufinamide 처방 1달 후 31.3%의 환자에서 발작 빈도가50% 이상 감소하였으며 6.3%의 환자에서 완전히 발작이 없어진 것을 확인하였다. 발작 빈도가 50% 이상 감소한 환자군은 처방 6달 후에도 50% 이상 감소한 상태로 유지되었고, 6개월 후 3.1% 의 환자에서 완전히 발작이 없어진 것을 확인하였다. 28.1%의 환자에서 부작용이 나타났으며 부작용은 구역, 구토, 식욕부진, 활동도 저하, 기면, 공격성향, 타액분비 등이었다. 결론: 본 연구를 통해 레녹스-가스토 증후군과 같은 난치성 뇌전증을 가진 소아에서 rufinamide를 효과적이고 안전하게 사용할 수 있다는 것을 확인하였다. Purpose: Rufinamide (RFM) is known to be effective for children with Lennox-Gastaut syndrome (LGS). The aim of this study is to evaluate its efficacy and tolerability of Korean children with LGS. Methods: This is a single center, open label, retrospective study. Patients with LGS who received rufinamide as adjunctive therapy were enrolled in this study. Their baseline clinical characteristics, the percent change in the seizure frequency per 4 weeks, and adverse events were evaluated. Results: Among 32 children, 20 were males and the mean age was 11.3±6.6 years. After 1 month of rufinamide medication, the frequency of seizures was reduced by more than 50% in 31.3% of patients and 6.3% of patients had no seizures. After 6 months of rufinamide administration, patients with a 50% or less decrease in seizure frequency remained in a state of reduced seizure frequency and 3.1% of patients had no seizures. Side effects such as nausea, vomiting, anorexia, less active, somnolence, aggression, drooling were noted in 28.1% of patients. Conclusion: This study suggests that rufinamide can be considered as an effective and safe treatment option for intractable epileptic children such as LGS. KCI Citation Count: 0